UV light and the ocular lens: a review of exposure models and resulting biomolecular changes - MacFarlane, Emily R.; Donaldson, Paul J.; Grey, Angus C. (Frontiers in Ophthalmology, 2024)
UV light is known to cause damage to biomolecules in living tissue. Tissues of the eye that play highly specialised roles in forming our sense of sight are uniquely exposed to light of all wavelengths. While these tissues have evolved protective mechanisms to resist damage from UV wavelengths, prolonged exposure is thought to lead to pathological changes. In the lens, UV light exposure is a risk factor for the development of cataract, which is a condition that is characterised by opacity that impairs its function as a focusing element in the eye. Cataract can affect spatially distinct regions of the lens. Age-related nuclear cataract is the most prevalent form of cataract and is strongly associated with oxidative stress and a decrease in the antioxidant capacity of the central lens region. Since UV light can generate reactive oxygen species to induce oxidative stress, its effects on lens structure, transparency, and biochemistry have been extensively investigated in animal models in order to better understand human cataract aetiology. A review of the different light exposure models and the advances in mechanistic understanding gained from these models is presented.